Complete Remission of the Severe Advanced Stage Cancer by miRNA-Mediated Transcriptional Control of Bcl-xL with Huaier Therapy Compared to the Conventional Chemotherapy with Platinum (II) Complex - Tanaka, Manami; Tanaka, Tomoo; Teng, Fei; Lin, Hong; Li, Ning; Luo, Zhu; Sadahito, Sotaro; Suzuki, Toshiyuki; Wei, Ding; Lu, Zhengxin (Archives of Clinical and Biomedical Research, 2021)
Background: The severe advanced stage cancer has scarce choice of treatment except pain control. Conventional chemotherapy is commonly not applicable for these patients from severe adverse events and toxicity. Objective: We have initiated genome-scope project for precise comprehension of anti-cancer effects of Huaier, with a comparison to the results by the treatment with platinum (II) complex (FOLFOX6, FOLFIRINOX, and Cisplatin: CDDP). Methods: The RNA samples from the obtained peripheral blood from the volunteer patients were analyzed by total RNA and non-coding small RNA sequencing on BGISEQ-500 Platform. KEGG pathway classification was hired for the analysis of the obtained information of transcripts in the present study (https://www.genome.jp/kegg/). Results: Here we present the successful remission and recovery from the severe advanced stage of 1) oesophageal squamous cell carcinoma, 2) pancreatic adenocarcinoma, and 3) colorectal adenocarcinoma. The complete remission was obtained in the patients treated with Huaier only, and Huaier and FOLFIRINOX combined therapy, although poor prognosis was predicted in these patients if only treated with platinum (II) complex chemotherapy, such as Cisplatin: CDDP, FOLFOX, or FOLFIRINOX. The efficacy of the treatment could be easily and typically confirmed by the improvement of the image analysis with a significant decrease of tumor markers such as CEA, CA19-9, and DUPAN-2 by the time course of Huaier administration. The KEGG pathway classification indicated the key for the recovery was the inhibition of Bcl-xL, which altered and rescued impaired function of multiple signal transduction pathways enhancing apoptosis, especially through the intrinsic mitochondria-mediated pathway. These changes were caused by the miRNA-mediated transcriptional control as reported. In contrast, platinum (II)